KEPEMIMPINAN BERBASIS ETIKA : SEBUAH KAJIAN TEORITIS - Herni Herawati (Jurnal Ilmiah Manajemen dan Akuntansi, 2024)
Leadership plays an important role in the success of an organization, be it a non-profit organization. This research examines the importance of ethics in leadership as well as various leadership theories, including autocratic, laissez-faire, and democratic types. Ethical leadership includes managers' behavior and actions that reflect values and integrity, which play an important role in management performance and employee satisfaction. The research method used consists of qualitative and descriptive methods using literature and journals as sources of information. The research results show that good leadership not only directs and motivates employees to achieve goals, but also aligns behavior across all levels of the organization to ensure consistent and effective safety.  The relationship between leadership style and organizational ethics is so strong that it influences work culture and overall employee performance.